Equation Modelling of Automotive Textiles for Car Seat Covers in the Ghanaian Upholstery Industry - Dr. Richard Selase Gbadegbe; Edem Kwami Buami; Charles Kumah; Bijou Asemsro; Prof. Maxwell Selase Akple, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2023)
Among the many materials utilized in the production of automotive components are textile materials. Long-term use of vehicle seats causes the textile material used to cover the seats to degrade. Because of this, drivers and vehicle owners critically inspect such deteriorated car seat covers before getting a new one. This study is aimed at identifying the various factors that influence drivers and vehicle owners’ decisions about the choice of seat covers. In addition, to determine the factors that influence customers’ perception of locally manufactured seat covers by upholstery artisans. Structured questionnaire and online google form were used to collect data from 1042 respondents across the 16 regions of Ghana. The five main factors that customers focused on were identified using Principal Component Analysis (PCA) with Varimax rotation. Structural Equation Modelling (SEM) was used to predict the perception factors of local upholstery artisans and customers using the Smart PLS software. Textile resistance and accessibility, durability, quality, perception and aesthetics were the selection factors. The findings showed that consumers of automotive textile materials take into account the aforementioned aspects before making purchases, therefore manufacturers should pay attention to these factors to increase efficiency. The study concludes that local upholstery artisans need to concentrate on these factors in their operations.